Characterisation of two desiccation-linked dehydrins from Xerophyta humilis - Fan, Cynthia (Department of Molecular and Cell Biology, 2017)
In response to abiotic stresses, organisms throughout the plant kingdom, as well as microorganisms and micro-animals such as nematodes or tardigrades, have been observed to express Late Embryogenesis Abundant (LEA) proteins as protective mechanisms. However, despite two decades of research, little is understood about their physiological functions and this has led to extensive nomenclature, with a large amount of redundancy. The primary reason for this lack of insight into LEA protein functions is their highly hydrophilic and intrinsically disordered nature. Intrinsically disordered proteins (IDPs) cannot be studied using conventional methods of structural analyses such as X-ray crystallography and, therefore, alternative techniques are required. A combination of transgenic and in vitro studies have also shown that LEA proteins are most likely to behave as molecular chaperones by binding water and ions, preventing macromolecular aggregation and protecting enzymatic activity during dehydration. This study characterized two dehydrins that were expressed during dehydration in the desiccation tolerant plant, Xerophyta humilis. From a transcriptome analyses on X. humilis, cDNA for the two dehydrins were obtained. These sequences were first analysed using various in silico tools in order to identify putative dehydrin-specific characteristics. Subsequently, these two dehydrins were cloned and expressed for production of recombinant dehydrin protein. These proteins were then analysed in terms of structural and functional characteristics. Structurally, through the use of circular dichroism in an in vitro system, both dehydrins demonstrated the shift towards being increasingly alpha-helical when placed in environments of decreasing water content. The role of these two dehydrins in stabilizing enzymes during dehydration was subsequently investigated using citrate synthase (CS) and lactate dehydrogenase (LDH). The preservation of enzyme activity was observed in both CS and LDH. This preservation of enzyme activity was further maintained by the presence of trehalose. Anti-aggregation roles were also investigated, however, neither dehydrin demonstrated significant ability to minimize the aggregation of LDH. This study hopes to establish a pipeline for characterizing LEA proteins using structural and functional assays in order to provide alternative means of LEA protein classification.